Longitudinal Changes in Gambling, Buying and Materialism in Adolescents: A Population-Based Study - Estévez, Ana; Jauregui, Paula; Momeñe, Janire; Macía, Laura; Lopez-Gonzalez, Hibai; Iruarrizaga, Icíar; Riquelme-Ortiz, Conchi; Granero, Roser; Fernandez-Aranda, Fernando; Vintró-Alcaraz, Cristina; Mestre-Bach, Gemma; Munguía, Lucero; et al. (International journal of environmental research and public health, 2021)
Gambling disorder, gambling-related cognitive biases, compulsive buying, and materialistic values lead to impaired functioning in important areas of life. The aims of the present longitudinal study are (1) to evaluate the change produced after one year in those mentioned variables and (2) to examine the gender role in these changes and to analyze the mediational mechanisms among the variables of the study. The sample was composed of 182 adolescents (103 females and 79 males) from secondary education Spanish institutions who completed self-administered questionnaires. Structural equation modeling has been used to explore associations between the different variables. Our results show significant decreases in compulsive buying, materialism, and cognitive biases related to gambling after one year. Gambling disorder severity was directly related to cognitive distortions of gambling and being a man. Compulsive buying was associated with older age and the female gender. Materialism was associated with compulsive buying and the male gender. In conclusion, gambling disorder, gambling-related cognitive biases, compulsive buying, and materialistic values change over time in different ways, according to gender. The understanding of gambling disorder and compulsive buying in adolescents could potentially lead to early prevention and treatment programs for the specific needs of gender and age.
Keywords: adolescence; compulsive buying; gambling cognitions; gambling disorder; longitudinal; materialism; treatment; Scopus; WOS(2)